EXPLORING A TAILORED TASK-BASED LANGUAGE TEACHING (TBLT) MODEL FOR ENHANCING LANGUAGE PROFICIENCY IN MATURE STUDENTS - Adjei-Mensah, Susana (Universitas Islam Sumatera Utara (UISU), 2025)
Language teachers employ a range of approaches, both direct and indirect, to support effective language learning. Among these, Task-Based Language Teaching (TBLT) stands out as a learner-centred, indirect method that fosters critical thinking, problem-solving, and learner autonomy. Mature students in higher education, however, encounter distinctive challenges related to balancing multiple responsibilities, managing academic anxiety, addressing financial constraints, and overcoming limited language proficiency, often resulting from an extended gap in formal study. This paper proposes a tailored TBLT model comprising four components: constructivist principles, TBLT phases, cooperative learning principles, and contextually relevant teaching–learning activities. The model aims to enhance mature students’ language competence and bridge proficiency gaps with their younger peers through authentic tasks such as event planning, community debates, report writing, and formal email preparation. By drawing upon their professional and life experiences in these collaborative and authentic contexts, learners engage with real-world language use, leading to measurable improvements in linguistic performance. Implemented over a twelve-week intervention with 21 mature students at a private university, the model demonstrated significant gains in reading, writing, and speaking proficiency. The study thus presents an empirically validated framework integrating constructivist, task-based, and cooperative learning approaches to meet the specific needs of mature language learners.